A Non-Heme Diiron Complex for (Electro)catalytic Reduction of Dioxygen: Tuning the Selectivity through Electron Delivery - Wang, Lianke; Gennari, Marcello; Cantú Reinhard, Fabián G; Gutiérrez, Javier; Morozan, Adina; Philouze, Christian; Demeshko, Serhiy; Artero, Vincent; Meyer, Franc; de Visser, Sam P; Duboc, Carole (Journal of the American Chemical Society, 2019)
In the oxygen reduction reaction (ORR) domain, the investigation of new homogeneous catalysts is a crucial step toward the full comprehension of the key structural and/or electronic factors that control catalytic efficiency and selectivity. Herein, we report a unique non-heme diiron complex that can act as a homogeneous ORR catalyst in acetonitrile solution. This iron(II) thiolate dinuclear complex, [FeII 2(LS)(LSH)] ([Fe 2 SH ] + ) (LS2– = 2,2′-(2,2′-bipyridine-6,6′-diyl)bis(1,1-diphenylethanethiolate)) contains a thiol group in the metal coordination sphere. [Fe 2 SH ] + is an efficient ORR catalyst both in the presence of a one-electron reducing agent and under electrochemically assisted conditions. However, its selectivity is dependent on the electron delivery pathway; in particular, the process is selective for H2O2 production under chemical conditions (up to ∼95%), whereas H2O is the main product during electrocatalysis (less than ∼10% H2O2). Based on computational work alongside the experimental data, a mechanistic proposal is discussed that rationalizes the selective and tunable reduction of dioxygen.